“Were present, listened, approved…”: The functioning of the Warsaw Women’s Progymnasium according to the minutes of the meetings of the Pedagogical Council in 1914 - Oksana Drach; Iryna Ivakhnenko (Київські історичні студії, 2022)
Overcoming the uniformity of interpretations presented in the scientific literature, led to the expediency of focusing the search in a limited subject field. The empirical material of the research is the documents of the Warsaw Women’s Progymnasium, in particular the minutes of the meetings of the Pedagogical Council of the Institution for the second half of the 1913–1914 academic years. The task is to study the governing body’s work and analyse specific processes of educational activities and specific situations in this field. The methods used are the microhistorical approach, the cognitive strategies are the methodology of “understanding” and the concept of “rational explanation”. It is proved that the competence of the Pedagogical Council of the Warsaw Women’s Progymnasium included the whole complex of educational and ﬁnancial issues of the institution’s functioning. The eﬀorts of the Pedagogical Council headed by the Head of the Progymnasium were aimed at ensuring the appropriate level of educational training for students. The systematic work of the Pedagogical Council covered constant control of the educational eﬀectiveness of students from preparatory to graduating classes, clariﬁcation of problem situations, and ﬁnding a way out of them. An integral part of the monitoring was the educational process in the Progymnasium. The principles of spiritual development of female students included the concepts of Russian citizenship, moral and religious values, and culture. The discipline of students and their attitude to educational responsibilities determined the behavioral grade, approved by the Pedagogical Council. Exemplary behaviour and educational diligences were the criteria for assigning social assistance from the Progymnasium to low-income students.